Incidence and seasonality of type 1 diabetes: a population-based 3-year cohort study using the National Database in Japan. Issue 1 (29th September 2020) - Nishioka, Yuichi; Noda, Tatsuya; Okada, Sadanori; Myojin, Tomoya; Kubo, Shinichiro; Higashino, Tsuneyuki; Ishii, Hitoshi; Imamura, Tomoaki
Abstract : Introduction: To investigate the incidence of type 1 diabetes by age group (0–19, 20–39, 40–59, ≥60 years) in Japan and whether there is seasonality in this incidence. Research design and methods: The incidence of type 1 diabetes from September 2014 to August 2017 was estimated using 2013–2018 data from the National Database of Health Insurance Claims and Specific Health Check-ups of Japan. The incidence rate was analyzed using Tango's Index and the self-controlled case series method. Results: Overall, 10 400 of the 79 175 553 included individuals were diagnosed with type 1 diabetes. The incidence of type 1 diabetes from September 2014 to August 2017 was 4.42/100 000 person-years. The incidence rates for men aged 0–19, 20–39, 40–59, and ≥60 years were 3.94, 5.57, 5.70, and 3.48, respectively. Among women, the incidence rates for the same age ranges were 5.22, 4.83, 4.99, and 3.31, respectively. Tango's index showed that the incidence rate of type 1 diabetes was significantly associated with seasons among those aged 0–19 years. Further, the self-controlled case series method showed a significant interaction between age and season, with the incidence of type 1 diabetes being higher in spring for patients younger than 20 years of age. Conclusions: In Japan, men aged 40–59 years and women aged 0–19 years are the groups with the highest incidence of type 1 diabetes. Further, the incidence of younger-onset diabetes in Japan was higher in spring (from March to May).